Oral medication administration practice of nurses in Chitwan Medical College - Rajbanshi, L (Journal of Chitwan Medical College, 2017)
Administering medication is high risk activity because one third of the errors occur during the nurse administration phase. Objective of the study was to find out the nurses practice of administering medicine to the patients. For that onduty nursing supervisors were observed the activities of nurses during administering medicines to the patients at 6 pm, 10 pm and 6 am of following day. Out of 52 nurses, only 5.76% nurses asked patients about the history of allergy and 86.53% asked patients to state their name for identification, 55.76% of nurses compared label of drug with cardex while withdrawing from the stock, 38.46% while pouring and 40.38% before replacing the drug on stock., 13.46% nurse explained purpose of drug to patient, 94.23% were check expiry date of drug, 46.15% stayed with patient till swallowing of drug. This study revealed, 68.42% nurses used measuring cup for accurate measurement of the liquid drug. Similarly, transparency of the syrup was checked by the 50.0% of nurses and 73.60 % of nurses shook the drug(suspension) before pouring on cup. As nurses were poorly adhere to the medication administration procedure, development of policy and procedure with ongoing education and monitoring of practice on safe medication is recommended.